Effect of Cottonseed Meal as Substitute for Soybean Meal on the Egg Production and Egg Quality in Breeder Japanese Quail Diets - Arda Yıldırım; Ergin Öztürk (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine the effect of cottonseed meal (CSM) incorporated into laying rations in place of soybean meal (SBM) at different ratios on yield traits. The birds began to lay at 6th week, 180 female and 45 male quails were used in laying period experiment. Birds were fed with rations containing 20% CP and 3000 Kcal/kg ME up to 20-week age (Laying period). CSM as a substitute, five different rations of the protein content (0, 30, 58, 86 and 100%) for SBM to basal diets based on corn-soybean meal were used. The results showed that there were no differences in terms of egg yield traits, cumulative feed consumptions and viabilities during the laying period. The highest dry shell rate and shell thickness were obtained from 5th group and 1st group, respectively. As a result, adding CSM instead of SBM in laying period were no significantly differences in terms of egg production and egg quality in laying period.